Islam, the State, and Political Authority
IX, 255 p.
Keywords: The expert essays in this volume deal with critically important topics concerning Islam and politics in both the pre-modern and modern periods, such as the nature of government, the relationship between politics and theology, Shi'i conceptions of statecraft, notions of public duty, and the compatibility of Islam and democratic governance.